Effect of Mechanical Activation of Highly Disperse SiO₂/α-Fe₂O₃ Mixtures on Distribution of Valence Electrons - Zaulychnyy, Ya.V.; Gun’ko, V.M.; Yavorskyi, Y.V.; Zarko, V.I.; Piotrowska, S.S.; Mishchenko, V.M. (Металлофизика и новейшие технологии, 2015)
The crystal and electronic structures of SiO₂/α-Fe₂O₃ mixtures are analysed using X-ray diffraction and ultra-soft X-ray emission spectroscopy. The energy redistributions of the Fesрd, Sisp, and Op valence electrons due to changes in the mass ratio (20/80, 50/50, 80/20) of SiO₂ and α-Fe₂O₃ in the mixtures are studied. The ultra-soft FeLα, SiLα, and OKα X-ray emission spectra of SiO₂/α-Fe₂O₃ mixtures are compared with those of individual iron oxide and silica powders. Interatomic interactions of surface atoms of adjacent particles occur owing to high local pressures and temperatures under mechanical treatment of the composition. Electrons’ transfer from silicon cations to oxygen anions is observed as a result of the mechanical activation of SiO₂/α-Fe₂O₃ mixtures. Енергетичний перерозподіл Fesрd-, Sisp- та Op-валентних електронів через зміну масового співвідношення (20/80, 50/50, 80/20) вхідних прекурсорів SiO₂ та α-Fe₂O₃ у сумішах досліджували, порівнюючи одержані від них Рентґенівські емісійні спектри FeLα-, SiLα- та OKα-смуг із спектрами порошкового, чистого оксиду заліза та чистого діоксиду кремнію. Аналіза спектрів показала, що міжатомова взаємодія між поверхневими атомами відбувається внаслідок високих локальних тисків і температур при нашаруванні наночастинок діоксиду кремнію на частинки оксиду заліза. Внаслідок механоактивації відбувається перенесення електронів від катіонів Силіцію до аніонів Оксиґену досліджуваної суміші. Энергетическое перераспределение Fespd-, Sisp- и Op-валентных электронов за счёт изменения массового соотношения (20/80, 50/50, 80/20) входных прекурсоров SiO₂ и α-Fe₂O₃ в смесях исследовали, сравнивая полученные от них рентгеновские эмиссионные спектры FeLα-, SiLα- и OKα-полос со спектрами порошкового, чистого оксида железа и чистого диоксида кремния. Анализ спектров показал, что межатомное взаимодействие между поверхностными атомами происходит вследствие высоких локальных давлений и температур при наслоении наночастиц диоксида кремния на частицы оксида железа. В результате механоактивации происходит перенос электронов от катионов кремния к анионам кислорода исследуемой смеси.